Transparency, entrepreneurship and competitiveness - Ίκκος Άρης (SPOUDAI Journal of Economics and Business, 2006)
It is argued, with reference to the practices of the Greek society, that Corruption and Lack of Transparency block development and in this way impact negatively on the competitiveness and wealth creation of societies practicing them. This is because corruption and lack of transparency can not coexist with true Entrepreneurship, the latter to be understood in terms of Schumpeter's Entrepreneurs as society's pioneering force "Creatively Destroying" society's resources and established modes. Entrepreneurship, which is therefore a risk taking activity par excellence, will only flourish in a transparent, corruption-free environment based on fair play. Social trust and a focus on results rather than bureaucratic processes is the basis of this environment. JEL Classification: Z13: social norms and social capital, social networks